2021
DOI: 10.1101/2021.03.08.21253093
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anti-SARS-CoV-2 Serology persistence over time in COVID-19 Convalescent Plasma Donors

Abstract: Background: Characterizing the kinetics of the antibody response to SARS-CoV-2 is of critical importance to developing strategies that may mitigate the public health burden of COVID-19. We sought to determine how circulating antibody levels change over time following natural infection. Methods/Materials: We conducted a prospective, longitudinal analysis of COVID-19 convalescent plasma (CCP) donors at multiple time points over a 9-month period. At each study visit, subjects either donated plasma or only had stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…However, in obese COVID-19 patients, a reverse association has been observed between high BMI and lower SARS-CoV-2 antibodies [41]. In addition, the increase of SARS-CoV-2 antibodies in the second survey was associated with age older, higher BMI, more severe disease [42] and low current smoke. A hypothesis was suggested that a tobacco mosaic RNA virus, presented in the respiratory tract of smokers, could have some protection against the SARS-COV-2 virus [43].…”
Section: Discussionmentioning
confidence: 88%
“…However, in obese COVID-19 patients, a reverse association has been observed between high BMI and lower SARS-CoV-2 antibodies [41]. In addition, the increase of SARS-CoV-2 antibodies in the second survey was associated with age older, higher BMI, more severe disease [42] and low current smoke. A hypothesis was suggested that a tobacco mosaic RNA virus, presented in the respiratory tract of smokers, could have some protection against the SARS-COV-2 virus [43].…”
Section: Discussionmentioning
confidence: 88%
“…However, in obese COVID-19 patients, a reverse association has been observed between high BMI and lower SARS-CoV-2 antibodies [41]. In addition, the increase of SARS-CoV-2 antibodies in the second survey was associated with age older, higher BMI, more severe disease (42) and low current smoke. A hypothesis was suggested that a tobacco mosaic RNA virus, presented in the respiratory tract of smokers, could have some protection against SARS-COV-2 virus (43).…”
Section: Discussionmentioning
confidence: 88%
“…The surface-exposed location of the spike glycoprotein makes it a major target of neutralizing antibodies [16]. An in-house developed fluorescence reduction neutralizing assay (FRNA; not authorized by FDA; sensitivity and specificity data not available) [17] was performed to detect neutralizing antibodies against the SARS-CoV-2 virus (NT50) in all 140 CCP samples [14].…”
Section: Sars-cov-2 Virus Neutralizing Assaymentioning
confidence: 99%
“…These C19-kodecytes are agglutinated in the presence of SARS-CoV-2 antibodies using routine serologic platforms. We perform a clinical evaluation of this C19-kodecyte assay in CCP donors previously assessed with 2 commercial immunoassays and a virus neutralizing assay [14]. Amendments of 1988 (CLIA), were used to detect total binding antibodies against the SARS-CoV-2 virus in all 140 CCP donors [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation